1889 N.C. Sess. Laws 502, ch. 527, § 1. - (:unkn) unknown (General Publisher, 1889)
That it shall be unlawful for any person to point any gun or pistol at any person, either in fun or otherwise, whether such gun or pistol be loaded or not loaded.
--
Keywords: BRANDISHING